A cross-sectional chart of stretched penile length for Turkish children aged 0-6 years (Annals of Medical Research, 2021)
Aim: Examination of the external genitalia is an important step in the routine child examination. Penile lengths of infants of different ethnicities show statistically significant differences. Therefore, standard values for penis sizes in healthy newborns and children in each country should be established. The aim of this study was to establish a normal range of 0 to 6 aged healthy children stretched penile length and to evaluate the relationship between stretched penis length and height. Material and Methods: This was a cross sectional observational study, carried out at tertiary university hospital in Turkey. Total of 948 healthy children aged 0-6 years were included in the study. Stretched penile length (SPL) was measured from the pubic ramus to the tip of the glans. The mean stretched penil length and Stretched penile length / height ratio for each age group were calculated and percentile curves were determined for both group.Results: The stretched penile length was 2.76 ± 0.42 cm in full-term newborns (n = 101). The SPL ranged from 2.98 ± 0.44 cm to 3.40 ± 0.56 cm in aged 1.1 to 12 months (n=309). The SPL ranged from 3.62 cm to 4.96 cm in children aged 12.1 to 72 months (n=538). There was a statistically significant correlation between mean stretched penis length and height (p=0.001).Conclusion: These data may be useful in the follow-up of healthy children. Furthermore, this study sets an example for larger-scale studies performed using older participants population in a larger geographic region.
Keywords: Height; stretched penile length; SPL; Turkish children